Need of Practical Training to Commerce Graduates and Post-Graduates! - Kedare, Shubhangi M. (SFIMAR Research Review, 2018)
Education is an important weapon which makes a man self-reliant and self-dependent. Independent. In Mahatma Gandhi’s own words, "Education ought to be for children a kind of insurance against unemployment. India has one of the largest Higher Education system in the world. Over the last two decades, India has remarkably transformed its higher education landscape. It has created widespread access to low-cost high-quality university education for students of all levels. With well-planned expansion and a student-centric learning-driven model of education, India has not only bettered its enrolment numbers but has dramatically enhanced its learning outcomes. Without a proper education system, a country can’t develop. The educated citizens can bring the real development in a country. That is why all the developed countries spend major share of the GDP on the health and education sector. In India, only 75 per cent students have enrolled themselves in the formal education system. Compared to the developed country, these numbers are not good enough. In the developed countries the statistics are above 90 per cent. Few steps can be taken by the government and universities in India to improve the education system in this country. Sophisticated and innovative learning approaches in higher education will improve quality in the fast-changing education industry. Employers complain that many graduates they hire are deficient in basic skills such as writing, problem solving and critical thinking that college leaders and their faculties consistently rank among the most important goals of an undergraduate education. There is need to transform the curriculum. It should be progressive in nature. Indian education system is exam based but it should be career focussed or skill based. This will not only enable the young graduates and post-graduates to seek better employment opportunities but also will ensure the employability of students to greater extent. This research will throw light on evaluation of existing higher education system followed by University of Mumbai for commerce stream and suggestions to enhance the quality of higher education. This paper is based on primary data collected from professors, students and industry and corporate professionals in Mumbai.